Pt-nanoparticle functionalized carbon nano-onions for ultra-high energy supercapacitors and enhanced field emission behaviour - Suryawanshi, Sachin R.; Kaware, Vaibhav; Chakravarty, Disha; Walke, Pravin S.; More, Mahendra A.; Joshi, Kavita; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2015)
In the present work, we have investigated the charge storage capacitive response and field emission behaviour of platinum (Pt) nanoparticles decorated on carbon nano onions (CNOs) and compared them with those of pristine carbon nano onions. The specific capacitance observed for Pt-CNOs is 342.5 F g(-1), about six times higher than that of pristine CNOs, at a scan rate of 100 mV s(-1). The decoration with Pt nanoparticles, without any binder or polymer separator on the CNO, leading to enhanced supercapacitance is due to easy accessibility of Na2SO4 electrolyte in the active material. The Density Functional Theory (DFT) calculations of these systems reveal enhancement in the Density of States (DOS) near the Fermi energy (E-F) on account of platinum decoration on the CNOs. Furthermore, the field emission current density of similar to 0.63 mA cm(-2) has been achieved from the Pt-CNOs emitter at an applied electric field of similar to 4.5 V mu m(-1) and from the pristine CNOs sample current density of similar to 0.4 mA cm(-2) has been achieved at an applied electric field of similar to 6.6 V mu m(-1). The observed enhanced field emission behavior has been attributed to the improved electrical conductivity and increased emitting sites of the Pt-CNO emitter. The field emission current stability of the Pt-CNO emitter over a longer duration is found to be good. The observed results imply multifunctional potential of Pt-CNOs, as supercapacitor material in various next generation hybrid energy storage devices, and field emitters for next generation vacuum nano/microelectronic devices.